Sosialiasi Parenting untuk Peningkatan Kualitas Pendidikan Keluarga Milenial - Hidayati, Zuhriyyah; Ariyanti, Irma (TAAWUN, 2022)
Partners in Community Service (PKM) activities are PKK in Bangeran Village, Dukun District, Gresik Regency. The main problem that became the background of this socialization was the lack of information, insight, and parenting knowledge possessed by PKK cadres in Bangeran Village even though the majority of cadres were millennials. The purpose of this activity is to socialize parenting models that are in line with today's challenges, namely parenting for millennial parents. The methods of socializing parenting activities this time were lectures, questions and answers, and discussions. The results of this activity are full support from village officials who enthusiastically facilitate the implementation of this activity in full, the enthusiasm of PKK cadres who actively participate in parenting activities to completion, and the willingness of participants to learn and share experiences related to parenting. It is hoped that there will be a follow-up activity in the form of a parenting series considering that this parenting activity is the first to be held in Bangeran Village, Dukun District, Gresik Regency. This activity in itself became new information for PKK cadres who were present in terms of parenting or parenting.